Implementasi Pembelajaran Salat Sempurna untuk Penguatan Profil Pelajar Pancasila di Bimbingan Belajar (Bimbel) Dusun Kayumas Desa Ngrogung Ngebel Ponorogo - Murtadhiatul Fatikhir Rouf; Miftaku Ni'amah (Social Science Academic, 2023)
This study aims to describe the implementation of salat sempurna (perfect prayer) learning in community-based tutoring (bimbingan belajar/bimbel) as a medium for strengthening the Pancasila Student Profile. The research employed a field research design with a qualitative approach. The participants were 12 children from Dusun Kayumas, Ngrogung Village, Ngebel District, who attended tutoring sessions after completing their Madrasah Diniyah (Madin) classes. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The findings reveal that the implementation of salat sempurna learning had a positive impact on improving children’s understanding and skills in both recitations and prayer movements. Moreover, the program fostered values of discipline, cooperation, and noble character in line with the dimensions of the Pancasila Student Profile. Supporting factors included the involvement of ustadzah (religious teachers), KPM students, and the use of the mosque as a learning venue. Challenges encountered were limited time, varying levels of prior knowledge, and differences in learning motivation. Nevertheless, the Asset-Based Community Development (ABCD) approach proved effective in utilizing community assets, making the program more efficient and sustainable. This study highlights the importance of tutoring as an alternative form of non-formal education for enhancing worship practices and strengthening children’s character development.